2008
DOI: 10.1095/biolreprod.107.067041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ITGA4/ITGB7 and ITGAE/ITGB7 Expressing Subsets of Decidual Dendritic-Like Cells Within Distinct Microdomains of the Pregnant Mouse Uterus1

Abstract: Several leukocyte populations have been described within the pregnant mouse uterus, some of which express the integrin beta 7 (ITGB7). Here we demonstrate that the majority of the ITGB7(+) decidual leukocytes belong to the dendritic cell (DC) lineage. By multiparameter flow cytometric analysis we demonstrated the existence of three distinct DC subsets, characterized by differential expression of ITGA4/ITGB7 (formerly alpha4beta7-integrin) and ITGAE/ITGB7 (formerly alphaEbeta7-integrin). Importantly, the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Moreover, abalation of DCs also affects the accumulation of mature uNK cells (Krey et al, 2008). An impaired trafficking of CD11c + CD11b + DC cells to the pregnant uterus are accompanied with aberrant uNK differentiation in lower numbers and with smaller cell size (Behrends et al, 2008; Karsten et al, 2009), suggesting that DC-derived signals may directly mediate uNK homing and maturation in the pregnant endometrium, as reviewed (Blois et al, 2011). A milestone for understanding the fetomaternal immune tolerance is a unique Act-mOVA transgenic mouse model, which express the transmembrane form of ovalbumin (OVA) under the control of the ubiquitous β-actin promoter.…”
Section: Molecular Basis Of Decidualizationmentioning
confidence: 99%
“…Moreover, abalation of DCs also affects the accumulation of mature uNK cells (Krey et al, 2008). An impaired trafficking of CD11c + CD11b + DC cells to the pregnant uterus are accompanied with aberrant uNK differentiation in lower numbers and with smaller cell size (Behrends et al, 2008; Karsten et al, 2009), suggesting that DC-derived signals may directly mediate uNK homing and maturation in the pregnant endometrium, as reviewed (Blois et al, 2011). A milestone for understanding the fetomaternal immune tolerance is a unique Act-mOVA transgenic mouse model, which express the transmembrane form of ovalbumin (OVA) under the control of the ubiquitous β-actin promoter.…”
Section: Molecular Basis Of Decidualizationmentioning
confidence: 99%
“…DCs have been reported to recognize foreign antigens present on sperm cells upon mating (49, 50, 116), but most likely also recognize alloantigens expressed by the invasive trophoblasts during implantation and decidualization. Interestingly, upon implantation, DCs re-localize to different areas of the decidua (117). In particular, Erlebacher and co-workers have suggested that the decidua works as a barrier that impedes DCs to efficiently prime T-cells in the lymphoid organs, to minimize the immune response to paternal alloantigens (118).…”
Section: On Other Important Cellsmentioning
confidence: 99%
“…(C) Gating scheme and representative histograms showing the appearance of CFSE + migratory DCs in the uterine LNs. Cells were gated on B220 -cells to exclude B cells and thus help clarify the MHCII hi CD11c int migratory DC population (see Figure 1E versus decidua nor assess their migratory potential (10). Interestingly, another report that demonstrated a requirement for uterine CD11c + cells in the decidual response itself found these cells, in aggregate, to be largely F4/80 + (6).…”
Section: Figurementioning
confidence: 99%
“…Since the pregnant uterus contains a complex mixture of leukocytes that variably express DC markers such as CD11c (6,(8)(9)(10), our analysis first required visualizing DC emigration from the nonpregnant uterus in order to identify those cells with true LN-homing potential. Upon embryo implantation, some migratory DCs come to reside within the decidua but, remarkably, remain uninvolved in T cell recognition of the fetus and placenta.…”
Section: Introductionmentioning
confidence: 99%